1985
DOI: 10.1111/j.1471-4159.1985.tb04024.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Immunocytochemical Localization of Myelin Proteolipid Protein and Myelin Basic Protein to Oligodendrocytes in Rat Brain During Myelination

Abstract: Electron microscopic immunocytochemical studies were carried out to localize myelin basic protein and myelin proteolipid protein during the active period of myelination in the developing rat brain using antisera to purified rat brain myelin proteolipid protein and large basic protein. The anti-large basic protein serum was shown by the immunoblot technique to cross-react with all five forms of basic protein present in the myelin of 8-day-old rat brain. Basic protein was localized diffusely in oligodendrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
28
1
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 42 publications
6
28
1
1
Order By: Relevance
“…At 10 days staining of myelin sheaths was observed. The temporal appear ance of immunocytochemical staining in our study, perinuclear and then in myelin, agrees with the studies of Nussbaum and Roussel [35] and Schwob et al [36], At 10 days, un like previous ages examined, the protein was found everywhere that the mRNA is found. Both protein and mRNA are observed throughout the subcortical white matter but are excluded from the cingulum at this age.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…At 10 days staining of myelin sheaths was observed. The temporal appear ance of immunocytochemical staining in our study, perinuclear and then in myelin, agrees with the studies of Nussbaum and Roussel [35] and Schwob et al [36], At 10 days, un like previous ages examined, the protein was found everywhere that the mRNA is found. Both protein and mRNA are observed throughout the subcortical white matter but are excluded from the cingulum at this age.…”
Section: Discussionsupporting
confidence: 82%
“…In situ hybridization studies reveal a strong signal in many cells at 7 days, although only a few cells with perinuclear staining are observed by immunocytochemistry. Previous studies have demonstrated that the PLP protein is expressed in the Golgi apparatus prior to its expression in myelin [35,36], The perinuclear staining we ob served is most likely staining of the proteins in the Golgi. While the in situ studies may be more sensitive than the immunocytochemical studies [our Northern blots are more sen sitive than our Western blots (data not shown)], the perinuclear staining at this stage indicates that this is the site of greatest protein within these cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hartmann et al [1982] reported that MBP was inte grated in myelin sheaths before PLP. and Schwob et al [ 1985], using an immuno-electron microscopic approach, demonstrated that the first oligodendroglial ensheathments were MBP' and PLP . Immunohistolocalization of GalC on tis sue sections is not very easy to perform.…”
Section: Discussionmentioning
confidence: 99%
“…MBP and PLP stabilize apposed myelin membrane surfaces in compact myelin, and their transport routes are segregated. Thus, following its biosynthesis at the rough endoplasmic reticulum and processing through the Golgi apparatus (9,10), the transmembrane protein PLP is transported via vesicles to the myelin membrane (11,12). In marked contrast, MBP, a peripheral membrane protein facing the cytoplasm, is synthesized at and associates with the myelin membrane on site, involving myelin membrane-directed transport of its mRNA rather than the native protein (13,14).…”
mentioning
confidence: 99%